2000
DOI: 10.1063/1.1150295
|View full text |Cite
|
Sign up to set email alerts
|

Specific modification of polysulfone with cluster bombardment with assistance of Ar ion irradiation

Abstract: Objective: To develop a rapid method for the modification of polysulfone with ammonium sulfamate with the assistance of Ar ion irradiation with a multi-source cluster deposition apparatus. These surfaces mimicking the structure of heparin, a bioactive molecule, have a high anti-thrombosis property. Experimental Design: Polysulfone film, setting on a turning holder, was irradiated by Ar ions during bombardment with ammonium sulfamate clusters. The Ar ion source serves for the activation of a polymer surface and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As shown in Figure , another method for grafting sulfur moieties to a substrate is plasma immersion ion implantation (PIII) or its variants such as ionic cluster deposition . Both techniques utilize high potential differences to embed the fragments of sulfur moieties and Ar + ions into the substrates.…”
Section: Sulfonate–sulfate (So3–so4) Plasma Polymerized and Treated Smentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure , another method for grafting sulfur moieties to a substrate is plasma immersion ion implantation (PIII) or its variants such as ionic cluster deposition . Both techniques utilize high potential differences to embed the fragments of sulfur moieties and Ar + ions into the substrates.…”
Section: Sulfonate–sulfate (So3–so4) Plasma Polymerized and Treated Smentioning
confidence: 99%
“…Both techniques utilize high potential differences to embed the fragments of sulfur moieties and Ar + ions into the substrates. In PIII, the sulfur was evaporated into an ionization chamber while ionic cluster deposition bombarded the substrates with ammonium sulfamate clusters . The ionic cluster deposition method showed that sulfur with a S2p XPS binding energy of 167.6 eV was immobilized on the PE substrates in the absence of Ar + ions .…”
Section: Sulfonate–sulfate (So3–so4) Plasma Polymerized and Treated Smentioning
confidence: 99%